Oxygen atom ordering on SiO2/4H-SiC 0001 polar interfaces formed by wet oxidation. (December 2021) - Saito, Mitsuhiro; Li, Hongping; Inoue, Kazutoshi; Matsuhata, Hirofumi; Ikuhara, Yuichi
Abstract: In the processing of 4H-SiC MOSFET devices, it is crucial to optimize the condition of wet oxidation based on the wafer surface orientation to obtain excellent electronic properties. However, the mechanism of surface oxidation and the effect of surface polarity remain unclear. The atomic structures of SiO2 /4H-SiC (0001) [Si-face] and ( 000 1 ¯ ) [C-face] interfaces can be analyzed by aberration-corrected STEM and first-principles MD calculations. On the Si-face, interfacial O atoms on the amorphous SiO2 layer show clear atomic ordering with a rigid O-Si bridge structure across the SiO2 /4H-SiC interface, involving a slow oxidation rate. The C-face can be rapidly oxidized, resulting in dangling bonds, bond bending, rough interface, and residual carbon in the SiO2 . A key feature is the formation of a stable and flat oxidation front by O atom ordering and then the suppression of interface defects or residual C, which provides an approach for designing high-performance 4H-SiC MOSFET devices. Graphical abstract: In 4H-SiC MOSFET devices, initial stage of wet oxidation in SiO2 /4H-SiC interface plays key role to obtain excellent device properties. STEM imaging and MD calculation reveal O-atom-ordering in the amorphous SiO2 layer. This O-atom-ordering provides strong O-Si bridge structure with crystalline 4H-SiC and then the formation of atomically flat wide oxidation front without any defects, such as dangling bonds. Image, graphical abstract